Olivine avoidance behaviour by marine gastropods (Littorina littorea L.) and amphipods (Gammarus locusta L.) within the context of ocean alkalinity enhancement - Gunter Flipkens; Vincent Dujardin; Jordy Salden; Kyle T’Jollyn; Raewyn M. Town; Ronny Blust (Ecotoxicology and Environmental Safety, 2024)
Gigaton scale atmospheric carbon dioxide (CO2) removal (CDR) is needed to keep global warming below 1.5 °C. Coastal enhanced olivine weathering is a CDR technique that could be implemented in coastal management programmes, but its CO2 sequestration potential and environmental safety remain uncertain. Large scale olivine spreading would change the surficial sediment characteristics, which could potentially reduce habitat suitability and ultimately result in community composition changes. To test this hypothesis, we investigated the avoidance response of the marine gastropod Littorina littorea (Linnaeus, 1758) and marine amphipod Gammarus locusta (Linnaeus, 1758) to relatively coarse (83 – 332 µm) olivine and olivine-sediment mixtures during short-term choice experiments. Pure olivine was significantly avoided by both species, while no significant avoidance was observed for sediment with 3% or 30% w/w olivine. For L. littorea, aversion of the light green colour of pure olivine (i.e. positive scototaxis) was the main reason for avoidance. Moreover, olivine was not significantly avoided when it was 7.5 cm (45%) closer to a food source/darker microhabitat (Ulva sp.) compared to natural sediment. It is inferred that the amphipod G. locusta avoided pure olivine to reduce Ni and Cr exposure. Yet, a significant increase in whole body Ni concentrations was observed after 79 h of exposure in the 30% and 100% w/w olivine treatments compared to the sediment control, likely as a result of waterborne Ni uptake. Overall, our results are significant for ecological risk assessment of coastal enhanced olivine weathering as they show that L. littorea and G. locusta will not avoid sediments with up to 30% w/w relatively coarse olivine added and that the degree of olivine avoidance is dependent on local environmental factors (e.g. food or shelter availability).